Effects of soybean oil supplement to diets of lactating dairy cows, on productive performance, and milk fat acids profile: a meta-analysis. Issue 1 (2nd January 2019) - Mahdavi, Ali; Mahdavi, Ata; Darabighane, Babak; Mead, Andrew; Lee, Michael R. F.
Abstract: The aim of this paper was to investigate the effects of soybean oil, an oilseed rich in the polyunsaturated fatty acid C18:2, on dry matter intake (DMI), milk yield (MY) and milk composition (including fatty acid profile) of dairy cows by using a meta-analysis approach. In the meta-analysis, effect size for all outcomes was reported as standardised means difference with 95% confidence intervals. Q test and I 2 were calculated to detect the heterogeneity, with a meta-regression also used to investigate sources of heterogeneity. Results of the meta-analysis indicated that adding soybean oil to the diet of dairy cows decreased DMI, milk fat percentage (MFP), milk fat yield (MFY) and milk protein percentage (MPP), whilst significantly increasing MY. Unsaturated fatty acids C18:2, C18:1 trans-11 and C18:2 cis-9 trans-11 conjugated linoleic acid (CLA) all significantly increased with soybean oil inclusion in the diet, whereas C18:3 was numerically higher but not significantly different. Milk composition, including MFP, MFY, MPP, short-chain and medium-chain fatty acids (C4–C20) and unsaturated fatty acids showed a significant percentage of heterogeneity. Results of the meta-regression indicated that dose of soybean oil, total fatty acids in the diet, and the concentration of C18:2 between groups receiving soybean oil and control are the most important factors affecting this heterogeneity. By performing meta-analysis and meta-regression it can be concluded that dietary supplementation of soybean oil to lactating dairy cows decreased DMI, and increased MY and the amount of unsaturated fatty acids in milk. Highlights: Soybean oil dietary supplementation to dairy cows increased milk yield but reduced milk fat content. Milk fat in soybean oil dietary supplemented cows has a lower content of short-chain fatty acids, associated with de novo synthesis. Milk fat in soybean oil dietary supplemented cows has a higher content of C18:1 trans-11, C18:2 and CLA.